(3ZjK GdYGQV aj eYGQVI GHf GdaGQVs - (3CHh GdYHGS CMeO Hf jMji Hf CHi MLdI GdeZQHjs; (3GHf GdaGQV (B- (3SdWGf GdYGTbjf , YeQ Hf Ydj Hf eQTO Hf Ydj GdMehj, TQa GdOjf CHh MaU CHh GdbGSe,J (B632 (3g` s
(3BNQgG (B:s
(3aJGhi ai Mb GHf GdaGQV s
(3YdjgG JhbjY GdHOQ GdHTJcis
(3JHUQI GdYfhGf (B:s
(3eYGQVIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B216s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B504 s
Keywords: (3GdCOHs